VCAM-1 ABLATION IN NON-HEMATOPOIETIC CELLS IN MxCre+ VCAM-1(f/f) MICE IS VARIABLE AND DICTATES THEIR PHENOTYPE - Ulyanova, Tatiana (2007)
OBJECTIVE: The goal of the present study was to assess the extent of VCAM-1 gene deletion in hematopoietic vs. non-hematopoietic cells in the bone marrow (BM) of MxCre(+)VCAM-1(f/f) mice and its impact on the phenotypic features of these mice. METHODS: VCAM-1 ablation was evaluated at the genomic level by PCR, at the mRNA level by real time PCR and at the protein level by FACS and immunohistochemistry. The homing or mobilization of CFU-Cs was assessed by standard assays. RESULTS: A previously accepted Interferon-induction scheme yielded efficient VCAM-1 ablation in hematopoietic cells, but variable ablation in BM fibroblasts and endothelial cells. The level of ablation in the latter populations correlated with alterations in the hematopoietic phenotype. CONCLUSIONS: Poly(I:C)-induced MxCre-mediated gene ablation is highly efficient in hematopoietic cells, but variable and partial in non-hematopoietic cells in BM. Ablation of VCAM-1 in hematopoietic cells does not contribute to their mobilization, nor does it impair their homing. The latter is dependent on VCAM-1 ablation in non-hematopoietic cells of BM.